Structuring of an evaluation model of informational services in a library of an educational institution - Cavalcanti, Cláudia Osvaldina dos Passos; Dutra, Ademar; Soares, Sandro Vieira; Ensslin, Leonardo (Contextus - Revista Contemporânea de Economia e Gestão, 2023)
This study aims to structure an evaluation model of informational services performed by the library of an educational institution. To this end, the Multicriteria Methodology for Decision Support-Constructivist (MCDA-C) was used, obtaining, as main results: (1) the identification of 41 Primary Elements of Evaluation (PEEs) and 75 Concepts, which resulted in five areas of concern; (2) the identification of five performance indicators of the "Basic Services", being one descriptor with “Commitment” performance, three descriptors with “Market” performance and one descriptor with “Excellence”; and (3) the proposition of improvement actions through the 5W2H technique.